Reclassification of Ochrobactrum lupini as a later heterotypic synonym of Ochrobactrum anthropi based on whole-genome sequence analysis. Issue 8 (23rd May 2019) - Gazolla Volpiano, Camila; Hayashi Sant'Anna, Fernando; Ambrosini, Adriana; Brito Lisboa, Bruno; Kayser Vargas, Luciano; Passaglia, Luciane Maria Pereira
Abstract : The genus Ochrobactrum belongs to the family Brucellaceae and its members are known to be adapted to a wide range of ecological niches. Ochrobactrum anthropi ATCC 49188 T and Ochrobactrum lupini LUP21 T are strains isolated from human clinical and plant root nodule samples, respectively, which share high similarity for phylogenetic markers (i.e 100 % for 16S rRNA, 99.9 % for dnaK and 99.35 % for rpoB ). In this work, multiple genome average nucleotide identity (ANI) approaches, digital DNA–DNA hybridization (dDDH) and phylogenetic analysis were performed in order to investigate the taxonomic relationship between O. anthropi ATCC 49188 T, O. lupini LUP21 T, and other five type strains from the genus Ochrobactrum . Whole-genome comparisons demonstrated that O. lupini LUP21 T and the Ochrobactrum genus type species, O. anthropi ATCC 49188 T, share 97.55 % of ANIb, 98.25 % of ANIm, 97.99 % of gANI, 97.94 % of OrthoANI and 83.9 % of dDDH, which exceed the species delineation thresholds. These strains are also closely related in phylogenies reconstructed from a concatenation of 1193 sequences from single-copy ortholog genes. A review of their profiles revealed that O. anthropi ATCC 49188 T and O. lupini LUP21 T do not present pronounced differences at phenotypic and chemotaxonomic levels. Considering phylogenetic, genomic, phenotypic and chemotaxonomic data, O. lupini should be considered a later heterotypic synonym of O. anthropi .